The Future of Publications in the Humanities : Possible Impacts of Research Assessment - Žic Fuchs, Milena (2014)
This paper addresses the issue of how various approaches in evaluation of Humanities research outputs can affect publication landscapes in national contexts. The importance of 'visibility mechanisms' and their relation to 'assessment mechanisms' in the Humanities is discussed. Both 'visibility mechanisms' as well as 'assessment mechanisms' can impact the overall research output landscape and through this, also influence and trigger off changes in publication cultures. The question arises whether such developments can be avoided in cases when researchers, or communities of researchers, see them as negative, unwanted developments reflecting influences outside the disciplines themselves, and, their respective ways of producing and publishing research results. The ideal would be to allow unhindered development of publication cultures, development reflecting intra-disciplinary changes and needs for possible “new” outputs and, if possible, to avoid externally induced developments such as those that, for instance, can be called metrics induced changes. Whether this is possible in the context of the contemporary push towards evaluation and assessment of research remains an open question.
Projekt MZOS
ENG